Komunitas Makrozoobentos di Sungai Batang Gadis Kabupaten Mandailing Natal Sumatera Utara Community Makrozoobentos on the river of Batang Gadis at Mandailing Natal Regency in North Sumatra - Pahrurrozi Pahrurrozi; Pindi Patana; Ani Suryanti (AQUACOASTMARINE, 2015)
The river of Batang Gadis is the longest in Mandailing Natal and flows almost over the Mandailing Natal Regency. Starting from Pakantan Muara Sipongi, passing a couple of districts and Subdistrict in Muara Batang Gadis. This research focused on community of makrozoobentos and measurement of physical and chemical factors. The purpose of this research is to know the community of makrozoobenthos in the river of Batang Gadis, Mandailing Natal Regency, North Sumatra. This research was carried out in May-June 2014. Makrozoobentos retrieval used eckmangrabb and surber net, samples are sorted by using the method of hand sorting. The sample was identified in integrated laboratory USU. Research resulted 4 classes namely Gastropod, Chaetopoda, Insect, and Hirudinae, comprising 13 genera such as Terebia, makrozoobentos, Pila, Goniobasis Sphaerium, Pleurocera, Tryonia, Tubifex, Chironomus, Neophemera, Progompus, Glossiponia, Branchiura and Macromia. The highest density was from the genus of Tarebia with amount of 1259 ind/m2 which was found on the station 3 and the lowest was from the genus Glossiphonia respectively 3 ind/m2 found at station 1. The highest value of diversity (H') in the community makrozoobentos the highes was found in station 2 (Hʹ=1,55) and lowest in the sampling 3 station wish (Hʹ=0,626).Keywords: River of Batang Gadis, Structure Community, Makrozoobentos